2017
DOI: 10.1002/jclp.22468
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Randomized Preliminary Trial of a Modified Dissonance‐Based Eating Disorder Intervention Program

Abstract: Results provide preliminary support for the modified dissonance program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 53 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…This might be interpreted as providing additional support for the intervention theory for dissonance-based eating disorder prevention programs because the intervention activities center on exploring the costs of pursuing the thin ideal. Table 2 reveal that the trials that observed the largest effects (d > .70) for eating disorder symptoms, arguably the most critical outcome, emerged for the prevention programs evaluated by Atkinson and Wade (2016), Green et al (2016), Green, Willis et al (2017), Krishna (2011), Machin (2008), Mitchell et al (2007), and Rohde et al, 2014) relative to minimal intervention control conditions. Given that the studies by Machin, Mitchell, and Green, and Rohde evaluated interventions that added unique exercises to the standard Body Project the pattern of findings suggest that these versions of dissonance-based eating disorder prevention programs might be good candidates for implementation.…”
Section: Summary Of Average Effect Sizesmentioning
confidence: 99%
“…This might be interpreted as providing additional support for the intervention theory for dissonance-based eating disorder prevention programs because the intervention activities center on exploring the costs of pursuing the thin ideal. Table 2 reveal that the trials that observed the largest effects (d > .70) for eating disorder symptoms, arguably the most critical outcome, emerged for the prevention programs evaluated by Atkinson and Wade (2016), Green et al (2016), Green, Willis et al (2017), Krishna (2011), Machin (2008), Mitchell et al (2007), and Rohde et al, 2014) relative to minimal intervention control conditions. Given that the studies by Machin, Mitchell, and Green, and Rohde evaluated interventions that added unique exercises to the standard Body Project the pattern of findings suggest that these versions of dissonance-based eating disorder prevention programs might be good candidates for implementation.…”
Section: Summary Of Average Effect Sizesmentioning
confidence: 99%
“…When the Body Project group is part of multidisciplinary treatment, as was the case in the present study, one may also think about integrating the Body Project group with for example psychomotor and drama therapy elements. Green et al [ 11 ] and Rohde et al [ 25 ] already added unique exercises to the standard treatment protocol, increasing engagement and adding focus on the costs of social comparison, producing large treatment effects.…”
Section: Discussionmentioning
confidence: 99%
“…A novel dissonance-based intervention with university-aged couples involving interactive role plays, open discussion and interpersonal skills-building significantly reduced numerous key risk factors for EDs including environmental pressures to be thin, internalisation of the thin and athletic ideals, state body dissatisfaction, and actual-ideal body discrepancy [48]. Other smaller trials adapting this content to provide interactive interventions have also demonstrated CD's effectiveness at reducing ED symptomatology [49]. When delivered by trained facilitators to high school-aged females (i.e., ages 14-18 years), compared with the provision of education brochures, the 'Body Project' CD intervention was found to reduce body dissatisfaction in participants at up to three-years follow-up (FU) and decrease ED behaviours among girls considered 'high-risk' at one-year FU [41,42].…”
Section: Cognitive Dissonance-based Programsmentioning
confidence: 99%